COVID‐19 infection in a pediatric kidney transplant population: A single‐center experience. (3rd April 2021) - Singer, Pamela S.; Sethna, Christine; Molmenti, Ernesto; Fahmy, Ahmed; Grodstein, Elliot; Castellanos‐Reyes, Laura; Fassano, Jessica; Teperman, Lewis
Abstract: Background: The clinical course of SARS‐CoV‐2 in the pediatric kidney transplant population is not well described. Methods: We performed a retrospective cohort study of a pediatric kidney transplant population at a New York transplant center. Baseline characteristics and clinical course of patients with SARS‐CoV‐2 positivity (Ab or PCR) were described, and comparison between COVID‐positive and COVID‐negative transplant patients was performed. Results: Twenty‐two patients had COVID‐19 IgG testing performed, eight of whom also had PCR testing. 23% of our cohort had evidence of COVID‐19 infection. Four patients had positive IgG only, and one patient had a positive PCR. All five patients with a positive COVID test were female. Two patients had COVID‐19 symptoms, which were mild. Of the symptomatic patients, one had a positive PCR at time of symptoms, while the other had a negative PCR during symptoms but subsequently had positive IgG. As compared to patients with COVID‐19 negative results, those with COVID‐19 positivity were significantly more likely to have a known COVID‐19 exposure, and were also more likely to be female. There was no significant difference in time from transplant between the groups. Those in the COVID‐positive group had higher baseline antimetabolite dose and CNI troughs, although these did not reach statistical significance. Conclusions: Pediatric kidney transplant recipients are at risk for development of COVID‐19 infection. While this population may be more at risk for SARS‐CoV‐2 infection due to their immunosuppressed status, their clinical course appears mild and similar to a healthy pediatric population.